Health volunteers as environmental health monitors in food preparation, distribution and supply centers in the Covid-19 epidemic - Sahar Zamaniahari; moradali zareipour (Mashhad University of Medical Sciences, 2021)
The supervision of food preparation, distribution, and supply centers to maintain the health of users is the responsibility of inspectors and environmental health experts of medical universities across the country. Proper inspection and control of these centers play an important role in preventing the occurrence and prevalence of infectious diseases and protect the health of people in the community. Therefore, to prevent the spread of COVID-19 and the increasing number of patients with this disease, stricter control measures should be applied to food preparation, distribution, and supply centers, and health protocols should be inspected in these centers. Due to the shortage of environmental health forces, as well as the expansion of food preparation, distribution, and supply centers, the inspection of these centers and training of people in all centers regarding the observance of coronavirus prevention protocols are not possible. Therefore, the authors in this article suggest health volunteers as participants in overseeing food preparation, distribution, and supply centers. The active involvement and participation of health volunteers increase the sense of social responsibility and eliminate the sense of authority and dominance of formal organizations. After receiving face-to-face and virtual training on coronavirus prevention health protocols in food preparation, distribution, and supply centers, and visiting and monitoring several food centers alongside environmental health experts, health volunteers can carry out their activities for disease prevention and control. In this way, there will be a comprehensive determination to control the coronavirus in centers for the preparation, distribution, and supply of food. The results of these activities will have a positive effect on the health of people and society and ultimately the control of the disease.